Crystallography: Deep understanding the mechanism of -form nucleation in cooling crystallization of L-glutamic acid - Giang, Dang Truong; Quang, Khuc Chau; Thanh Huyen, Trinh Thi; Tuan, Nguyen Anh (Vietnam Journal of Chemistry, 2016)
The mechanism of heterogeneous β-form nucleation was investigated during the phase transformation of L-glutamic acid in the stirring cooling crystallization. In the present study, a new mechanism of heterogeneous β-form nucleation was explored, where the β-form nuclei was favorably crystallized on the (001) and (011) surfaces rather than the (111) surface of α-form crystal during the phase transformation. This result was confirmed via the molecular simulation, in which the functional groups of molecule on various surfaces of α-form crystal were different, so the degree of lattice matching (E) between the α-form substrate surfaces and β-form molecule aggregate was distinguished and ordered as (001) > (011) > (111), meaning that the nucleation of heterogeneous β-form was more facilitated on the (001) and (011) surfaces compared to that on the (111) surface of α-form crystal. Keywords. Crystallization, crystallography, polymorphism, nucleation, crystal growth.